The effect of constriction in hydraulic fracturing - He, J.; Pasternak, E.; Dyskin, A.; Lebedev, M.; Gurevich, Boris (2017)
© Springer International Publishing AG 2017. Fractures in geomaterials e.g., hydraulic fractures often contain bridges—parts of unbroken material connecting the opposite faces of the fracture distributed over the fracture and constricting its opening. Our laboratory experiments demonstrate that the bridges can even hold the sample cut through by a fracture together, in one piece. We model such a fracture as a crack with Winkler layer whose stiffness is controlled by the bridge geometry and distribution. The model shows that short constricted fractures are insignificantly different from the conventional cracks; only large fractures, i.e. the fractures whose size is of the order of the characteristic scale of the bridge constriction are affected. The constricted fractures have the opening and the Mode I stress intensity factor bound as the fracture dimensions proportionally increase, which distinguish them from the conventional cracks where both the opening and the stress intensity factors tend to infinity as the crack size increases.